Direct on Line Operation of Three Phase Induction Motor using MATLAB - Omar, Adil; Abdulrahman, Alaa M; Rashed, Ghamgeen I. (Sulaimani Journal for Pure and Applied Sciences, 2019)
Induction motors are most widely used motors due to their reliability, robustness and low cost. However, huge starting current and sudden change in load current of three phase induction motor are the most problems in high power applications since these lead to damage the motor. Therefore, controlling the current during transient is issential to protect the motor from damage. In order to control current instantaneously, it is required firstly to model the motor and secondly to represent the rotational three phase (current and voltage) instationary frame and this can be done using DQ modelling. The DQ modelling proposed in literature, the effect of friction was neglected and this reduces the correctness of the modelling. This Paper will look at the DQ modellingand method of starting up of the three phase induction motor. At first, the novilety of the this paper is to find the friction of the motor practically and include it in the DQ model. Then, itcalculating three phase induction motor parameters which will help in the modelling process Then, it usesthe direct on line method (DOL) to validate the DQ model using MATLAB/Simulink
Keywords: Three phase induction; Motor; Matlab Modeling